FIELD EXPERIENCE REPORT: NUTRITION EDUCATION FOR CHILD BASKETBALL TEAMS - Rodicheva, Natalia (My University, 2015)
Kansas State University was founded as a land-grant institution, and still holds to its mission to bring research to the community, and to disseminate and apply knowledge. For my field experience part of the MPH Nutrition program, I completed one hundred and eighty hours working with the Riley County Research and Extension office at 110 Courthouse Plaza, that is supported by Kansas State University. Required hours were completed between January 15, 2015 and March 12, 2015. In order to help the community to become a better place to live and work, the K-State Research and Extension office (Kansas Agricultural Experiment Station and Cooperative Extension Service) states that its goal is to assist the population technically and to provide evidence-based programs to the community. To fulfil this mission and provide resources and materials on agriculture, economics, family science and youth development as well as leadership and business to the community, the office partners with College of Agriculture, College of Arts and Sciences, College of Engineering, College of Human Ecology, and College of Veterinary Medicine. The structure of K-State Research and Extension office is shown in Figure 5-1. The Cooperative Extension was founded in 1914, and programs for the county were funded through government sources and land-grant university support (Kansas State University for Riley County). The Riley County Research and Extension office is run by the county extension director who works with extension agents, receptionist and assistants; extension agents work mostly in fields of family and consumer sciences, 4-H program, horticulture and agriculture (Riley County, 2014). Riley County Extension is an active participant of the Flint Hills Wellness Coalition, and is currently focusing on increasing access to healthier foods (vending, concessions) and creating a tobacco-free community (Riley County, 2014). Virginia (Ginny) Barnard was my supervisor for the field experience program. Ginny got her graduate degree in Public Health from Kansas State University and currently works as the Family and Consumer Sciences Agent for Riley County. Ginny is involved with numerous projects/programs for the Research and Extension Office regarding nutrition, food safety, healthy lifestyles and overall well-being. From January to March, 2015 I was involved in several projects that Ginny was in charge of, that fit my interests, skills and education. As a part of my field experience I had two big projects and several minor projects that required my participation. One of the programs I was involved in was nutrition education for school-aged children playing basketball through Parks and Rec program. Another important part of the field experience was the DIET FREE program (nutrition education and wellness for adults). I was also attending yoga sessions for elementary school kids with Ginny, and participating and leading one of the lunch series lectures at the City Hall in Manhattan, KS.
Keywords: Flint Hills Wellness Coalition; Family and Consumer Sciences; Diet Free program; Public Health (0573)